Relay Type 1a in LTE-Advanced: Can it increase energy efficiency? - Dimic, Goran; Bajic, Dragana; Beko, Marko (2014 XXXIth URSI General Assembly and Scientific Symposium (URSI GASS), 2014)
A comparison of energy efficiency of two-hop transmission via Type 1a relay node (RN) and the direct link in LTE-Advanced, between the same base station (BS) and user terminal (UE), is presented. We build upon an existing energy consumption model, which links the total transceiver power consumption as a function of transmitted power, channel loss along each of the three links, and PHY and protocol parameters. In the space of channel losses, we show equipotential planes of the energy consumption ratio in the transceivers' operating region. In the equivalent space of transmit powers, we show required power levels to enable certain constellation and coding rate pairs. Overlapping the two spaces quantifies the energy efficiency increase. The increase in energy efficiency by a single-digit multiplying factor is possible. It is achieved by maximizing transmit power along both relaying hops, and selecting the constellation size and code rate pair which maximizes data rate, subject to the reliability constraint.